Studying stress-strain state of gear billet using mathematical models depending on clamping forces in 3 and 6 cam self-centering chucks - A. S. Serkov; V. B. Masyagin; R. L. Artyuh; L. B. Serkova; V. V. Akimov (Омский научный вестник)
The article discusses the results of studies of the 3D model of the gear wheel by the finite element method (FEM) in the stressstrain state (VAT). The model is in a state of static equilibrium in the presence of various basing mechanisms. The novelty lies in the study of the effect of clamps on gears with various basing schemes in 3 and 6 cam chucks. Physical experiments are obtained (photomechanics).